Effect of defatted pepper (Capsicum annuum L.) seed extracts on high-fat diet-induced obesity in C57BL/6J mice - Sung, Jeehye; Yang, Jinwoo; Kim, Younghwa; Kim, Myunghee; Jeong, Heon Sang; Lee, Junsoo (Food science and biotechnology, 2016)
This study investigated the effect of defatted pepper seed ethanolic extract (DPSE) on high-fat diet-induced obesity in C57BL/6J mice. The mice were fed a normal diet (ND), high fat diet (HFD), or HFD in combination with DPSE (100 and 200mg/kg body weight) for 7 weeks. Supplementing the HFD of mice with DPSE significantly decreased body weight gain and food efficiency ratio induced by HFD. The amount of epididymal fat and size of adipocytes were also dramatically reduced by DPSE supplementation. Although no statistical significance was found between the HFD and HFD plus DPSE groups in plasma fat deposition, liver weight, and hepatic cholesterol contents were significantly reduced in the DPSE-treated group. In conclusion, these results suggest that DPSE could prevent obesity and adiposity. These effects may be important in developing therapeutic agents against obesity in future.